Environmental and health impact assessment from a heavy-duty diesel engine under different injection strategies fueled with a bioethanol–diesel blend. (1st October 2015) - Ballesteros, R.; Guillén-Flores, J.; Barba, J.
Highlights: Speciated diesel emissions are studied under different operating conditions. Atmospheric reactivity and toxicity assessments are also analyzed. Injection pressure and timing, air–fuel ratio and EGR rates effects are studied. Carbonyl and PAH emissions are, in most cases, higher with the ethanol blend. Reactivity and toxicity values are reduced with bioethanol, in most cases. Abstract: Different injection strategies have been widely studied in both multi- and single-cylinder diesel engines, testing different fuels. However, studies including hydrocarbons speciation are scarce or even inexistent. In the present work, carbonyl compounds (CCs) and particulate-associated polycyclic aromatic hydrocarbons (PAHs) emissions, from a heavy-duty single-cylinder diesel engine, have been analyzed under different operating conditions, testing a commercial diesel fuel and a bioethanol–diesel blend. The engine was coupled to a dynamometer and fully equipped with the different apparatus needed to characterize the engine performance and emissions. For CCs and PAHs analyses, a high performance liquid chromatography system was used. Results showed a general increase in both regulated and non-regulated emissions when the bioethanol–diesel blend was used. Regarding the different parametric studies, trends showed a decrease in CCs emissions when λ and injection pressure increased and multiple injections were used. Results also showed a maximum with the variation of the start of injection and an increase with the EGR rate. As for PAH, results presented a reduction with λ and an increase with the EGR rate, whereas the rest of parametric studies did not show any clear trend. With respect to reactivity and toxicity assessments, specific emission levels showed great relevance in final results.